Dam-Break Energy of Porous Structure for Scour Countermeasure at Bridge Abutment - Ira Widyastuti; M. Arsyad Thaha; Rita Tahir Lopa; Mukhsan Putra Hatta (Salehan Institute of Higher Education, 2022)
The aim of the study is to determine the structure for energy absorption in order to countermeasure the scouring on the bridge abutment. Consider a porous structure for energy absorption, which can reduce flow velocity and depth of scouring due to its porosity. The energy absorber plate demonstrated in triangular shape with several porous as submerged barrier. The investigation was conducted in laboratory and placed the abutment in the middle of the channel with a distance of 3Lb, 5Lb, 7Lb and 9Lb. The plate area consists of 0% (MP1), 5% (MP2), and 10% (MP3). The scour depth measurement (ds) is carried out at 6 crucial points in the abutment area. Comparisons between experimental measurements and a numerical prediction model are presented. The experimental results show that the percentage of frictional velocity in the inhibition area for each pore opening before the obstacle, 31.42% (decreasing), - 9.27% (increasing), and -32.92% (increasing), respectively. Furthermore, the optimum position of the porous energy absorber at 9Lb to the abutment. The magnitude decreases of scour depth obtained from MP2. It can be concluded that the placement of energy absorbers can lead to damping forces. It also found that the porous structures could be beneficial for motion damping and absorber of the scouring. Doi: 10.28991/CEJ-2022-08-12-019 Full Text: PDF